Coordination and Collective Performance: Cooperative Goals Boost Interpersonal Synchrony and Task Outcomes - Allsop, Jamie S.; Vaitkus, Tomas; Marie, Dannette; Miles, Lynden K. (Frontiers in Psychology, 2016)
Whether it be a rugby team or a rescue crew, ensuring peak group performance is a primary goal during collective activities. In reality however, groups often suffer from productivity losses that can lead to less than optimal outputs. Where researchers have focused on this problem, inefficiencies in the way team members coordinate their efforts has been identified as one potent source of productivity decrements. Here we set out to explore whether performance on a simple object movement task is shaped by the spontaneous emergence of interpersonally coordinated behavior. Forty-six pairs of participants were instructed to either compete or cooperate in order to empty a container of approximately 100 small plastic balls as quickly and accurately as possible. Each trial was recorded to video and a frame-differencing approach was employed to estimate between-person coordination. The results revealed that cooperative pairs coordinated to a greater extent than their competitive counterparts. Furthermore, coordination, as well as movement regularity were positively related to accuracy, an effect that was most prominent when the task was structured such that opportunities to coordinate were restricted. These findings are discussed with regard to contemporary theories of coordination and collective performance.